(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Today, this topic is very relevant, because the observance of ethical norms is an integral part of the presenter, TV programs and television companies as a whole. This determines the level of qualification and the fullness of the media. This article analyzes the trends and ethical issues of the talk show.